EXAMINING CHALLENGES IN RURAL ENGLISH EDUCATION - Sukma, Doris; Ristra, Pretti; Antika, Rindilla (Universitas PGRI Sumatera Barat, 2025)
Despite nationwide challenges in English language acquisition, students in geographically isolated regions like Bengkalis Island, Indonesia, face unique obstacles. Drawing upon the theoretical framework that posits the unique challenges of English teaching and learning in rural areas, this qualitative study delves into the specific challenges encountered by first-year students (n=537) at Politeknik Negeri Bengkalis, all of whom completed high school on the island. Through semi-structured interviews, the study explores these challenges and reveals common struggles with grammar, vocabulary, and pronunciation, similar to urban students. However, the influence of teacher competence and mother tongue interference emerge as potentially distinct challenges in this rural context. Understanding these unique obstacles can inform targeted interventions to enhance English language learning outcomes for students in isolated regions of Indonesia.